RISK MANAGEMENT FOR COOPERATIVES OF SAVINGS AND LOANS AND SHARIA FINANCING: LESSON FROM INDONESIA - Rizky ANDREAN; Muhammad Khoirul FIKRI; Santi Nailul IZATY (Management & Marketing, 2024)
This research aims to find out and describe the risks that exist in sharia financial institutions in the form of Cooperatives of Savings and Loans and Sharia Financing (KSPPS). This research uses a qualitative descriptive approach in the form of library research, which uses secondary data from journal articles and regulations relevant to the research topic. The research results show that there are various risks that KSPPS can experience. According to Minister of Labour Decree No. 193 of 2017, risk is the potential for financial losses and worsening social performance of Cooperatives of Savings and Loans and Sharia Financing/Sharia Business Units of Savings and Loans and Sharia Financing (KSPPS/USPPS). Based on these regulations, risk consists of strategic risk, financing risk, financial risk, and operational risk. Risk management in the management of KSPPS and similar institutions is an absolute priority to pay attention to. The risk often experienced by KSPPS is financing risk. Risk management in dealing with financing consists of risk analysis steps, which can be in the form of SWOT analysis, prudential analysis, 5C analysis, and 7P analysis, as well as risk handling mechanisms, which can be in the form of persuasive efforts, rescheduling, reconditioning, restructuring, combinations, and confiscation of collateral.